A Calcium/Calmodulin-regulated Member of the Receptor-like Kinase Family Confers Cold Tolerance in Plants - Yang, Tianbao (American Society for Biochemistry and Molecular Biology, 2010)
Cold is a limiting environmental factor that adversely affects plant growth and productivity. Calcium/calmodulin-mediated signaling is believed to play a pivotal role in plant response to cold stress, but its exact role is not clearly understood. Here, we report that CRLK1, a novel calcium/calmodulin-regulated receptor-like kinase, is crucial for cold tolerance in plants. CRLK1 has two calmodulin-binding sites with different affinities as follows: one located at residues 369–390 with a K(d) of 25 nm, and the other located at residues 28–112 with a K(d) of 160 nm. Calcium/calmodulin stimulated the kinase activity, but the addition of chlorpromazine, a calmodulin antagonist, blocked its stimulation. CRLK1 is mainly localized in the plasma membrane, and its expression is stimulated by cold and hydrogen peroxide treatments. Under normal growth conditions, there is no noticeable phenotypic difference between wild-type and crlk1 knock-out mutant plants. However, as compared with wild-type plants, the crlk1 knock-out mutants exhibited an increased sensitivity to chilling and freezing temperatures. Northern analysis showed that the induction of cold-responsive genes, including CBF1, RD29A, COR15a, and KIN1 in crlk1 mutants, is delayed as compared with wild-type plants. These results indicate that CRLK1 is a positive regulator of cold tolerance in plants. Furthermore, our results suggest that CRLK1 plays a role in bridging calcium/calmodulin signaling and cold signaling.